2019
DOI: 10.1016/j.cpc.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficient sampling of spreading processes on complex networks using a composition and rejection algorithm

Abstract: Efficient stochastic simulation algorithms are of paramount importance to the study of spreading phenomena on complex networks. Using insights and analytical results from network science, we discuss how the structure of contacts affects the efficiency of current algorithms. We show that algorithms believed to require O(log N ) or even O(1) operations per update-where N is the number of nodes-display instead a polynomial scaling for networks that are either dense or sparse and heterogeneous. This significantly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…For our simulations, we made use of the exceptionally fast implementation by St-Onge et al [76]. For simplicity, we set time units to be equal to the expected recovery time (such that γ = 1) and vary β over a large enough range to explore outbreaks of varied sizes.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…For our simulations, we made use of the exceptionally fast implementation by St-Onge et al [76]. For simplicity, we set time units to be equal to the expected recovery time (such that γ = 1) and vary β over a large enough range to explore outbreaks of varied sizes.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Rejection sampling for the efficient simulation of Markovian stochastic processes on complex networks has been proposed recently [24,25,26,34], but not for the non-Markovian case where arbitrary distributions for the inter-event times are considered.…”
Section: Our Methodsmentioning
confidence: 99%
“…However, both methods require computationally expensive updating of an agent's neighborhood in each simulation step, which renders them inefficient for large-scale networks. In the context of Markovian processes on networks, it has recently been shown that rejection-based simulation can overcome this limitation [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…. In this paper, the SIS prevalence is generated by an event-driven simulation based on the Gillespie algorithm (Gillespie 1977;Liu and Van Mieghem 2017;St-Onge et al 2019).…”
Section: The Sis Processmentioning
confidence: 99%